Evaluation of the SOFA score as a tool to predict DCI-associated infarctions after spontaneous subarachnoid hemorrhage - Kurz, Elena; Fassl, Verena; Brockmann, Carolin; Schulze, Alicia; Kalasauskas, Darius; Ringel, Florian; Neulen, Axel (Frontiers in Medicine, 2025)
BackgroundDelayed cerebral ischemia (DCI)-associated infarctions are a major complication after spontaneous subarachnoid hemorrhage (SAH). Besides cerebral pathophysiological effects, peripheral organ dysfunction has been associated with DCI. The Sequential Organ Failure Assessment (SOFA) score is used in intensive care medicine to monitor organ failure. The objective of our study was to compare the SOFA score obtained in the first 48 h post-SAH, Hunt & Hess (HH), and World Federation of Neurosurgical Societies (WFNS) scores in predicting DCI-associated infarctions and to identify the most robust parameters within the SOFA score.MethodsWe retrospectively evaluated SOFA, H&H, and WFNS scores and DCI-associated infarctions in a cohort of 253 SAH patients.ResultsThe ROC analysis revealed an AUC of 0.65 for the SOFA score in predicting DCI-associated infarctions (H&H: 0.64, WFNS: 0.62). The threshold that maximized the sum of sensitivity and specificity was ≥7 points (sensitivity of 0.58, specificity of 0.68, PPV of 0.20, NPV of 0.92). A simplified score using only the three most robust parameters of the SOFA score, GCS, mean arterial pressure, and the Horovitz quotient, resulted in an AUC of 0.7.ConclusionThe SOFA score predicted the development of DCI-associated infarctions similar to the established H&H and WFNS scores. A simplified score combining the three most robust parameters of the SOFA score was at least equal to the established scores. Therefore, the SOFA score and our simplified score could be used as an additional tool to identify SAH patients at high risk for DCI-associated infarctions.